MEDIASI DIGITAL LITERACY PADA PENGARUH TECHNOLOGY ADOPTION TERHADAP TECHNOSTRESS DI KALANGAN KARYAWAN INDONESIA - Zahra Haryadi; Angela Caroline; Agus Gunawan; Yoke Pribadi Kornarius (Media Bina Ilmiah, 2025)
This study aims to analyze the influence of Technology Adoption on Technostress, mediated by Digital Literacy among Indonesian employees. Using a quantitative approach, the study employs path coefficient regression analysis and Sobel test to examine four main hypotheses based on a sample of 188 respondents. The key findings indicate that digital literacy serves as a significant mediator, reducing the negative impact of technology adoption on technostress, the frequency distribution results reveal that the levels of Technology Adoption (TA), Technostress (TS), and Digital Literacy (DL) among Indonesian employees are predominantly within the category of agreement towards technology adoption and having adequate digital literacy. However, employees also exhibit uncertainty regarding technostress. Employees with high digital literacy are capable of managing the complexity of new technologies and can mitigate the psychological pressure associated with intensive technology use.